The role of social media in promoting environmental cultural identity among Saudi youth (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify the role of social media in promoting environmental cultural identity among Saudi youth. The study is a descriptive study, relying on a media survey approach. The study sample consists of (400) Saudi youth who use accounts that present environmental cultural content on social media. A questionnaire was used as a data collection tool.The study reached a number of results, the most important of which are:-      Saudi youth in the study sample prefer Snapchat in first place for following environmental content on social media, followed by TikTok in second place by a small margin, YouTube in third place, and Instagram in fourth place.-      The motive (to know the Kingdom's efforts in developing and preserving the environment) was found to be the foremost motive for the Saudi public in Al-Ahsa to follow the study sample, with a relative weight of (13.39%), followed by the motive (to watch environmental culture content supported by pictures and videos) in second place, with a relative weight of (13.32%). The study sample respondents chose the motive (to obtain information related to environmental culture content) in third place, with a relative weight of (12.88%).-      The Saudi youth in the study sample believe that the phrase (my knowledge about the Kingdom’s environmental cultural identity has increased) comes at the forefront of their attitudes towards the effects of social media sites in strengthening their environmental cultural identity, with an arithmetic mean of (2.72), followed by the phrases (I am proud of the Kingdom’s efforts in preserving the environment), and (I learned about the causes of climate change in the Kingdom and the countries of the world) in second place with an arithmetic mean of (2.69) for each of them.
Keywords: Social Media; Environmental Cultural Identity; Saudi Youth